Sistem Inventory Pada Gudang Aksesoris PT. Mulia Knitting Factory - Yohanes, Yohanes; Wahidin, Ahmad Jurnaidi (Jurnal Informatika, 2022)
Information can be obtained more easily and quickly because of the existence of information technology, one of the uses of information technology is the application of warehouse inventory. PT. Mulia Knitting Factory already has several applications that serve business processes including purchase transactions, stock up to payment processing. However, not all sections have implemented this. Because for now the existing application is only for the input and output of goods from the warehouse, for example in the accessories warehouse. The stock file is not only needed by the warehouse department, but also by the purchasing department. With manual data collection, the inventory of goods is not immediately updated, so that errors in raw material inventory information still often occur. The author makes a web-based inventory application design that will be used by the accessories warehouse section and then can also be viewed or controlled by the purchasing department so that it can make it easier to control the purchase of goods and accessories needed. The research was conducted using the waterfall method to build applications so that the resulting applications are better and of higher quality. The resulting application is then tested using black box testing with the results of all tests being accepted, so the application can be used.